KONSEPSI PERAN MATAHARI DALAM FOTOSINTESIS: SEBUAH METAFORA GURU IDEAL PENDIDIKAN AGAMA ISLAM - Aristya, Septian; Atmaja, Bondan Tri; Raihan, Raihan (Al-Rabwah, 2025)
Islamic education is essentially a process of developing a whole person, emphasizing not only cognitive aspects but also spiritual and social ones. However, contemporary educational approaches often neglect the contemplative and ecological dimensions. This study uses a qualitative approach based on literature review to explore the conceptual link between the role of sunlight in the process of photosynthesis and the role of teachers in Islamic Religious Education learning. The results of the study indicate that sunlight, as the primary trigger for photosynthesis, can be interpreted metaphorically as a teacher who illuminates and activates the spiritual potential of students. The intensity, quality, and direction of light represent the teacher's presence, competence, and moral orientation in the educational process. The conceptual implications of this study emphasize the importance of a reflective, ecological, and spiritual Islamic educational paradigm, where teachers function as sources of enlightenment on values ​​and life that integrate science and spirituality in learning practices.